MICROBIOLOGICAL MONITORING OF YERSINIA AS THE BASIS OF SANITARY AND EPIDEMIOLOGICAL SURVELLANCE OF YERSINIOSIS IN ORGANIZED GROUРS - A. L. Panin; L. A. Kraeva; V. B. Sboychakov; A. B. Belov; V. N. Bolekhan; D. Yu. Vlasov; G. Ya. Tseneva (Инфекция и иммунитет, 2014)
Abstract. Practical decision of infectology problem depends on the correct assessment of the main concepts of epidemiology and microbiology. The feasibility of attracting the attention of specialists in related disciplines to the problem of microbiological monitoring is discussed. In connection with the capabilities of highly sensitive molecular methods and mathematical modeling on the example of microbiological monitoring of Yersinia was made attempt to analyse mod- ern opportunities of bacteriology and to enter a predictive component as an important element of purposeful activity into monitoring definition. Yersiniosis are one of the most urgent infectious diseases. A variety of biological properties of Yersinia, their various epidemiological importance (Yersinia spp. enter into I, III and the IV groups of virulence), group incidence of Yersiniosis in the organized groups, mobility of genes of a virulence and change of pathogenic properties of Yersinia from strain to strain cause need of carrying out microbiological monitoring with a predictive component in new social and biological conditions.